The Passionate War the narrative history of the Spanish Civil War, 1936-1939 - Wyden, Peter (New York : Simon and Schuster, 1983)
"The Spanish Civil War was fought from 17 July 1936 to 1 April 1939 between the Republicans, who were loyal to the established Spanish Republic, and the Nationalists, a rebel group led by General Francisco Franco. The Nationalists prevailed, and Franco ruled Spain for the next 36 years, from 1939 until his death in 1975."--Wikipedia.
Includes index
Bibliography: p. [546]-555.
77140
Keywords: History -- 1936-1939. -- Spain